Effect of Service Quality to Customer Satisfaction Bank Mandiri - Galih Wisnu Wardhana; Agus Nugroho (Common Publisher, 2020)
The purpose of this research is to know the significance of tangible influence, reliability responsiveness, assurance and empathy to customer satisfaction at Bank Mandiri. The population in this study were Bank Mandiri customers in November 2019 when the study was taken a number of 100. Techniques to take samples done by convenience sampling. Analytical techniques in this study consisted of, instrument testing, classical assumption test, multiple linear regression analysis, t test, F test and R2 test. The result of this research proves that tangible and reliability have positive and significant influence on satisfaction, responsiveness and assurance have positive and insignificant effect to satisfaction, while emphaty have negative and insignificant effect on satisfaction. The result of F test shows that tangible, reliability, responsiveness, assurance, and emphaty variables significantly influence customer satisfaction variable. The result of R2 test (coefficient of determination) is known that tangible, reliability, responsiveness, assurance, and emphaty variable are able to explain 61,9% to satisfaction variable.